مسلم معاشرہ میں خانگی امور کے اصلاح کی معاصر اخلاقی تحدیات: سیرت النبی ﷺ کی روشنی میں ان کاحل : Contemporary Ethical Challenges in the Reform of Family Affairs in Muslim Society: Solutions in the Light of the Seerah of the Prophet (ﷺ) - Dr.Amjad Hayat (MEI, 2025)
In the contemporary era, humanity has amassed material comforts to create peaceful and comforting homes. Yet, despite these efforts, individuals remain trapped in chaos and distress. One major reason for this predicament is the moral deterioration of the fundamental unit of society—the family—whose ethical foundation has become hollow. Elevated and stable moral values within families play a crucial role in ensuring social stability and development. However, in modern times, particularly in Muslim households, there is a lack of ethical teachings such as kindness and good conduct, which has led to significant disruptions in family life. In Pakistani society, there is considerable negligence in the moral training and reform of family affairs, particularly in the relationship between spouses. This negligence has not only led to an increase in social issues but has also contributed to a rising trend of divorce. In this context, as humanity grapples with numerous ethical and social crises, it increasingly turns to the Seerah of the Prophet Muhammad ﷺ for solutions. The survival of the human race is also dependent on the stability of the family system, in which the Seerah of the Prophet ﷺ serves as a guiding light. This study will explore the dimensions of ethical challenges in the reform of family affairs in Pakistani society and investigate the ethical teachings from the Seerah of the Prophet ﷺ that offer solutions to these issues. It will also highlight how these moral teachings can be applied in the contemporary context to enhance ethical reform in family affairs. Keywords: Muslim Society, Challenges, Ethics, Family Issues, Prophetic Seerah, Reform.